A Bayesian approach to the identification of active location and dispersion factors. Issue 7 (2nd July 2016) - Yu, I Tang
ABSTRACT: In this article, we extend the modified Box–Meyer method and propose an approach to identify both active location and dispersion factors in a screening experiment. Since several candidate models can be simultaneously considered under the framework of Bayesian model averaging, the proposed method can overcome the problem of missing the identification of some active factors caused by either the alias structure or misspecification of the location model. For illustration, three practical experiments and one synthetic data set are analyzed.